Bio-oil production via solvolysis of oil palm empty fruit bunch using Zn-supported zeolite catalyst - Yao, Rachel Tang Duo (2017)
Biomass is one of the renewable energy that has been revealing its potential as a substituent for natural fossil fuels recently. Nowadays, converting biomass via liquefaction technology appears to be another alternative to obtain valuable high energy products such as biofuel, gas and char. In this study, oil palm empty fruit bunch (EFB) has been chosen as the source of biomass for biomass-to-biofuel conversion. The main focus of the study was on the presence of different composition of Zn supported on zeolite ZSM-5 as solid acid catalyst to enhance the production of bio-oil from the biomass. The prepared catalysts were characterized using X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), field-emission scanning electron microscope with energy-dispersive X-Ray spectroscopy (FE-SEM/EDX) and temperature-programmed desorption (TPD)–NH3. Gas chromatography mass spectroscopy (GC-MS) was employed for bio-oil analysis. Conversion of EFB to liquid products was carried out by using an autoclave. The production of bio-oil from EFB was subjected to a series of optimization tests: reaction temperature, reaction time, catalyst loading and catalyst composition. The optimum condition for the conversion of EFB to liquid products was achieved at 180°C for 90 min with 0.5wt% of 15% Zn supported on ZSM-5. Without the presence of the catalyst, there are many compounds found in the bio-oil such as aromatics compounds, phenols and others. In contrast, high selectivity towards the production of furfural (approximate 83% of total compounds in the bio-oil) was reported under optimum condition with the presence of catalyst. Phenols were also found to be the second highest compound obtained after furfural (~8.2%). This value-added product obtained in this study is a very useful chemical feedstock especially in adhesive industry.